Effect of green tea and tea catechins on the lipid metabolism of caged laying hens - ZHOU, Y B; WAN, X C; HU, J W; SHAO, L; SHANG, Y Y (The Indian Journal of Animal Sciences, 2012)
The present study was conducted to evaluate the effects of supplementing different levels of green tea or tea catechins on total cholesterol (TC), total triglycerides (TG), high-density lipoprotein (HDL), and low-density lipoprotein (LDL) levels in the plasma of laying hens, as well as the TC, TG and total fatty acid (TFA) levels in breast and thigh meat and egg yolk. Laying hens (1620), 16-week-old, were randomly assigned to 9 dietary groups. Each treatment had 180 birds with 3 replicates. The basal diet was respectively supplemented with green tea powder (0, 2, 4, 6, 8 g/kg) and tea catechins (0.5, 1, 1.5, 2 g/kg). Hens were then reared in battery cages for 60 days. Supplementation with 6 g/kg green tea and 1 g/kg tea catechins at day 56 lowered TC, TG and LDL levels in both plasma and meat, increased plasma HDL levels and decreased yolk TG levels, where statistical significance was considered quadratically. TC levels in yolk were not affected. The addition of green tea and tea catechins had no effect on the levels of myristic acid (C14: 0), stearic acid (C18: 0), oleic acid (C18: 1), linoleic acid (C18: 2n-6), arachidonic acid (C20: 4n-6) and TFA content in yolk, but increased the unsaturated fatty acid content. Dietary green tea and tea catechins increased the excretion of TFA in faeces compared to the control. These results suggest that the addition of green tea and/or tea catechins to the diet of laying hens can improve lipid metabolism and the fatty acid composition of egg yolk.